Syed Syeikh al-Hadi, sasterawan progresif Melayu - Talib Samat (Kuala Lumpur : Dewan Bahasa dan Pustaka, Kementerian Pendidikan, Malaysia, 1992)
Biography of Syed Syeikh al-Hadi, 1867-1934, Malaysian poet.
Includes bibliographical references (p. 195-197) and index.
Keywords: Sheikh bin Ahmad Al-Hadi, -- al-Syed, -- 1867-1934.; Authors, Malay -- Biography; Ulama -- Malaysia -- Biography